DHPLC Screening of ATM Gene in Italian Patients Affected by Ataxia-Telangiectasia: Fourteen Novel ATM Mutations. Issue 4 (9th June 2013) - Magliozzi, Monia; Piane, Maria; Torrente, Isabella; Sinibaldi, Lorenzo; Rizzo, Giovanni; Savio, Camilla; Lulli, Patrizia; De Luca, Alessandro; Dallapiccola, Bruno; Chessa, Luciana
Abstract : The gene for ataxia-telangiectasia (A-T:MIM:#208900), ATM, spans about 150~kb of genomic DNA and is composed of 62 coding exons. ATM mutations are found along the entire coding sequence of the gene, without evidence of mutational hot spots. Using DNA as the starting material, we used denaturing high performance liquid chromatography (DHPLC) technique to search for ATM gene mutations. Initially, DHPLC was validated in a retrospective study of 16 positive control samples that included 19 known mutations; 100% of mutations were detected. Subsequently, DHPLC was used to screen for mutations a cohort of 22 patients with the classical form of A-T. A total of 27 different mutations were identified on 38 of the 44 alleles, corresponding to a 86% detection rate. Fourteen of the mutations were novel. In addition, 15 different variants and polymorphisms of unknown functional significance were found. The high incidence of new and individual A-T mutations in our cohort of patients demonstrates marked mutational heterogeneity of A-T in Italy and corroborate the efficiency of DHPLC as a method for the mutation screening of A-T patients.